Acute Ischemic Stroke on Cancer Patients, a Distinct Etiology? A Case-Control Study - Romeiro, Ana Carrilho (2015)
Introduction: It is still unclear whether the etiology of ischemic stroke differs between cancer and non-cancer patients. Stroke and cancer share common modifiable risk factors but evidence suggests that cancer patients have specific conditions that increase the risk of stroke. Our goal was to compare the etiology of ischemic stroke in cancer and non-cancer patients.Material and Methods: Case-control study conducted in patients admitted to a stroke unit between January 2007 and December 2012. Cases had a concomitant diagnosis of cancer and acute ischemic stroke, controls of only stroke. Age, gender, vascular risk factors and etiology were compared between groups.Results: Fifty-six cases were identified; 64.3% were men with a mean age of 71 years; 21 patients had evidence of active cancer. Gastrointestinal cancer (25.9%) was the most common; 151 controls were included matched for gender and age. Common modifiable vascular risk factors, between groups (cases versus controls) were not significantly different, except for diabetes mellitus, more frequent in the control group (16.1% vs 33.8%, p = 0.02). Previous thrombotic events were more frequent in the cancer cohort (8.9% vs 0.7%, p = 0.007). Other determined etiology subtype (TOAST classification) was more frequent in cancer patients when compared to controls (13.0% vs 0.8%, p < 0.01), and a hypercoagulable state was significantly more prevalent in active cancer patients.Discussion: In our case-control study two subsets of cancer patients were delineated. In a subgroup, cancer and stroke co-exist, sharing traditional vascular risk factors. In another subset of patients, stroke appears to be directly related to the presence of a malignancy, where hypercoagulopathy turns out to be a decisive mechanism.Conclusion: In clinical grounds, hypercoagulopathy as stroke etiology should prompt the physician to screen the patient for occult cancer.